Relationship Community Knowledge About Covid 19 with Anxiety in The Working Area of 37 Gantiwarno Public Health Center Pekalongan, East Lampung in 2021 - Rini Palupi; Zenni Puspitarini; Ardinata Ardinata; Hamid Mukhlis (Universitas Aisyah Pringsewu, 2022)
The COVID-19 pandemic, which has hit almost all countries and contributed to the largest number of deaths in the last two years, has had a huge impact not only on society but also on various development sectors. In addition, the psychological impact also has an impact on residents' fear and anxiety to carry out activities outside the home which also affects the mental health of individuals who experience lifestyle changes with limited and limited socialization.This type of research is a quantitative descriptive study with a cross-sectional design to see the relationship between public knowledge about covid 19 and anxiety. This research plan will be located in the Working Area of 37gantiwarno Public Health Center sPekalongan, East Lampung. The research subjects are the people of Jojog Village who are in the working area of the 37gantiwarno Health Center with a sampling technique using simple random sampling totaling 357 people.The targeted mandatory output is the publication of scientific articles in accredited national journals in 2021. The TKT of this research is the Vaccine/Biological Health Type with the status of the basic principles of technology being researched and reported where the study of scientific literature on the basic principles of the technology developed already exists, the initial survey has started and assessed, and potential scientific applications for problem-solving have been described Abstrack: ini memberikan dampak yang sangat besar tidak hanya pada masyarakat tetapi juga pada berbagai sektor pembangunan. Selain itu dampak psikologis juga memberikan dampak ketakutan dan kecemasan warga untuk melakukan aktivitas di luar rumah yang berimbas juga terhadap kesehatan mental individu yang mengalami perubahan gaya hidup dengan sosialisasi yang terbatas dan dibatasi. Jenis penelitian ini adalah penelitian deskriptif kuantitatif dengan rancangan cross sectional untuk mengetahui hubungan pengetahuan masyarakat tentang covid 19 dengan kecemasan. Rencana penelitian ini akan berlokasi di Wilayah Kerja Puskesmas 37 Gantiwarno Pekalongan Lampung Timur. Dengan subjek penelitian adalah masyarakat Desa Jojog yang berada di Wilayah kerja Puskesmas 37 Gantiwarno dengan teknik pengambilan sampel menggunakan simple random sampling yang berjumlah 357 orang. Luaran wajib yang ditargetkan berupa publikasi artikel ilmiah dalam jurnal nasional terakreditasi tahun 2021. TKT penelitian ini adalah Jenis Kesehatan Vaksin/Hayati dengan status prinsip dasar dari teknologi diteliti dan dilaporkan dimana studi literatur ilmiah tentang prinsip dasar teknologi yang dikembangkan sudah ada, survey awal telah dimulai dan dinilai, dan potensi aplikasi ilmiah untuk pemecahan masalah telah digambarkan